The Concept Of Education In Islamic Schools: A Resume Report - Rika Sartika (The Progress: Journal of Language and Ethnicity, 2022)
This paper aim to identify the synthesis of education in the interpretation of thematic studies of the terms included in the connotation of education. This paper is the result of a literature review on terms that connote education in the Qur'an and al-Sunnah, namely tarbiyah, ta'lim, ta'dib, tadris, da'wah, irsyad, tadbir, tazkiyah, and uswah. This paper concludes that the nine terms that connote education in their respective contexts describe the concept of education in a complete synthesis, which is in line with the dynamics of humanity as God's representative on earth. The results of this study can be used to understand the nature of the terms included in the connotation of education and their implications for Islamic education.